Special Reserve : Jerusalem Print Workshop. (Jerusalem : Art Focus, 1994)
The screenprints were specially created by the artists for the catalogue and printed at the Workshop by Etan Hurwitz and Ophir Galler.
Special Reserve : Jerusalem Print Workshop, Larry Abramson, Asaf Ben-Zvi, Dganit Berest, Moshe Gershuni, Zvi Tolkovsky, Ra'anan Levy, Sharon Poliakine, Exhibition: Autumn 1994
Engels & Hebreeuws
kunstcatalogus
Keywords: Abramson, Larry; Ben-Zvi, Asaf; Berest, Dganit; Gershuni, Moshe; Tolkovsky, Zvi; Levy, Ra'anan; Poliakine, Sharon